Experimental Study on the Accumulation Characteristics and Mechanism of Landslide Debris Dam - Xie, Xiangping; Wang, Xiaojun; Zhao, Shenzhou; Li, Zhongli; Qin, Xuyang; Xu, Shu (Frontiers in Earth Science, 2022)
According to physical model tests, we analyzed the accumulation characteristics of landslide dams formed under three different slope characteristics including uniform slope, parallel slope and intersecting slope, and investigated the accumulation mechanisms of the debris dams. The relationship between the slope types and the accumulation characteristics was also explored using tracer particle analysis method. The damming process and accumulation mechanism of the landslide dam were changed with slope conditions, which leaded to the difference in the accumulation characteristics of the dam, especially in transverse cross-section shape and grain size distribution. The transverse cross-section shape of the landslide dams formed by different slope conditions can be divided into three categories: the flat pattern, the unidirectional pattern and the undulating pattern. The characteristics of the slope body are closely related to the landslide dam with respect to debris distribution. The debris distributions in the longitudinal and transverse directions of the slope body are consistent with those in the longitudinal and sliding regions of the dam. A general inverse grading characteristic of debris gains occurs in the vertical direction of landslide dams. For the uniform and parallel slopes, obvious inverse grading distribution is induced by overall-starting initiation of slope body and strong vertical infiltration of the fine sands during the movement. However, inverse grading distribution is generated by the effects of pushing-climbing and lateral infiltration existed among particles caused by a layered-starting mode for the intersecting slope body. This study provides a basis for the prediction of landslide-dam formation and backtrack the initial structure of the slope.